Cleaning heavy metal pollution of wastewater with compost application - Benjared, Ramadan; Füleky, György (Lviv Polytechnic Publishing House, 2016)
In the present study, a kinetic experiment investigated the adsorption of Zn, Cu and Cd from aqueous systems onto different compost materials. The treatment has been attempted via batch experiments under various solution concentrations. It probes mainly three adsorbents which their characteristics are as follow, 1. Felgyő is a green waste and sewage sludge. 2. Garé is a communal sewage sludge, slurry mud and chicken manure with straw. 3. Sioagárd is green biomass/ bio waste. The metal initial concentration solutions was ranging from 0 to 50000 μg/g as contaminants and 13 samples were prepared of mixing 10 ml of liquid with 1g of compost as one sample ,accordingly the fusion placed in shaker for 24 hours thus the combination was centrifuged, filtered and the heavy metal concentration was determined with atomic absorption spectrophotometry. Each heavy metal treatment was replicated three times for quality assurance and the kinetic data were well described by Langmuir model, hence Curves were plotted for the adsorption of heavy metal on the adsorbent. The maximum amount sorbate of heavy metal (Amax mgkg-1 ) is 44245 for Cu by Garé compost followed by Cd 40107 and less for Zn with record of 26803 by the same compost. Higher amounts were sorbed from Cd, Cu and less from Zn solutions. Characterization of the adsorbents was one of the key focal areas of experiment investigation. The result indicated that adsorption efficiency decreased with increase in the initial solution concentration. At lower heavy metal concentrations practically all of the heavy metals ions were removed by the compost application whereas in higher concentrations the fix value ratio of heavy metal ions decreased to 40 %, however the amount of the compost per sample remained with 1g.
Keywords: Heavy metal; compost; adsorption; wastewater; langmuir